PERAN MEDIASI KEPUASAN KONSUMEN PADA DETERMINAN KEPUTUSAN PEMBELIAN ULANG WEDANG UWUH HALAL - Dwi Karti Handayani; Lukia Zuraida (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
A brand trust that has been highly expected by consumers indicates the brandimage of the product is also high, thus moving consumers to make a purchase ofa product. The research method used in this study is quantitative with a crosssectional design. The sampling technique in this study used convenience sidetechniques with 100 respondents. The data collection method used a closedquestionnaire and the analysis technique used is PLS. The results showed thatproduct quality has a positive effect on customer satisfaction and repurchasedecision. Brand trust has a positive effects on customer satisfaction but has noeffect on repurchase decision. Consumer satisfaction has a positive effect onrepurchase decision. Consumer satisfaction mediates product quality and brandtrust on the repurchases decision of wedang uwuh halal.